A Flow Cytometry Method for Dissecting the Cell Differentiation Process of Entamoeba Encystation - Mi-ichi, Fumika; Miyake, Yasunobu; Tam, Vo Kha; Yoshida, Hiroki (Frontiers in Cellular and Infection Microbiology, 2018)
Amoebiasis is caused by Entamoeba histolytica infection, a protozoan parasite belonging to the phylum Amoebozoa. This parasite undergoes a fundamental cell differentiation process from proliferative trophozoite to dormant cyst, termed “encystation”. The cysts formed by encystation are solely responsible for the transmission of amoebiasis; therefore, Entamoeba encystation is an important subject from both biological and medical perspectives. Here, we have established a flow cytometry strategy for not only determining the percentage of formed cysts but also for monitoring changes in cell populations during encystation. This strategy together with fluorescence microscopy enables visualization of the cell differentiation process of Entamoeba encystation. We also standardized another flow cytometry protocol for counting live trophozoites. These two different flow cytometry techniques could be integrated into 96-well plate-based bioassays for monitoring the processes of cyst formation and trophozoite proliferation, which are crucial to maintain the Entamoeba life cycle. The combined two systems enabled us to screen a chemical library, the Pathogen Box of the Medicine for Malaria Venture, to obtain compounds that inhibit either the formation of cysts or the proliferation of trophozoites, or both. This is a prerequisite for the development of new drugs against amoebiasis, a global public health problem. Collectively, the two different 96-well plate-based Entamoeba bioassay and flow cytometry analysis systems (cyst formation and trophozoite proliferation) provide a methodology that can not only overcome the limitations of standard microscopic counting but also is effective in applied as well as basic Entamoeba biology.